Assortative mating, sexual selection, and their consequences for gene flow in Littorina. (12th June 2020) - Perini, Samuel; Rafajlović, Marina; Westram, Anja M.; Johannesson, Kerstin; Butlin, Roger K.
Abstract: When divergent populations are connected by gene flow, the establishment of complete reproductive isolation usually requires the joint action of multiple barrier effects. One example where multiple barrier effects are coupled consists of a single trait that is under divergent natural selection and also mediates assortative mating. Such multiple‐effect traits can strongly reduce gene flow. However, there are few cases where patterns of assortative mating have been described quantitatively and their impact on gene flow has been determined. Two ecotypes of the coastal marine snail, Littorina saxatilis, occur in North Atlantic rocky‐shore habitats dominated by either crab predation or wave action. There is evidence for divergent natural selection acting on size, and size‐assortative mating has previously been documented. Here, we analyze the mating pattern in L. saxatilis with respect to size in intensively sampled transects across boundaries between the habitats. We show that the mating pattern is mostly conserved between ecotypes and that it generates both assortment and directional sexual selection for small male size. Using simulations, we show that the mating pattern can contribute to reproductive isolation between ecotypes but the barrier to gene flow is likely strengthened more by sexual selection than by assortment.